Instant effects of changing body positions on compositions of exhaled breath. (18th November 2015) - Sukul, Pritam; Trefz, Phillip; Kamysek, Svend; Schubert, Jochen K; Miekisch, Wolfram
Abstract: Concentrations of exhaled volatile organic compounds (VOCs) may depend not only on biochemical or pathologic processes but also on physiological parameters. As breath sampling may be done in different body positions, effects of the sampling position on exhaled VOC concentrations were investigated by means of real-time mass spectrometry. Breaths from 15 healthy volunteers were analyzed in real-time by PTR-ToF-MS-8000 during paced breathing (12/min) in a continuous side-stream mode. We applied two series of body positions (setup 1: sitting, standing, supine, and sitting; setup 2: supine, left lateral, right lateral, prone, and supine). Each position was held for 2 min. Breath VOCs were quantified in inspired and alveolar air by means of a custom-made algorithm. Parallel monitoring of hemodynamics and capnometry was performed noninvasively. In setup 1, when compared to the initial sitting position, normalized mean concentrations of isoprene, furan, and acetonitrile decreased by 24%, 26%, and 9%, respectively, during standing and increased by 63%, 36%, and 10% during lying mirroring time profiles of stroke volume and pET-CO2 . In contrast, acetone and H2 S concentrations remained almost constant. In setup 2, when compared to the initial supine position, mean alveolar concentrations of isoprene and furan increased significantly up to 29% and 16%, respectively, when position was changed from lying on the right side to the prone position. As cardiac output and stroke volume decreased at that time, the reasons for the observed concentrations changes have to be linked to the ventilation/perfusion ratio or compartmental distribution rather than to perfusion alone. During final postures, all VOC concentrations, hemodynamics, and pET-CO2 returned to baseline. Exhaled blood-borne VOC profiles changed due to body postures. Changes depended on cardiac stroke volume, origin, compartmental distribution and physico-chemical properties of the substances. Patients' positions and cardiac output have to be controlled when concentrations of breath VOCs are to be interpreted in terms of biomarkers.